CUSTOMER SATISFACTION SURVEY AMONG STUDENTS AT THE UNIVERSITY OF CEBU LAPU-LAPU AND MANDAUE COLLEGE OF NURSING (UCLM-CN) FOR THE S.Y. 2022-2023 - Micabalo, Kingie; Cabasa, Aida; Sanchez, Marc; Lopez, Marcelo; Villarante, Carmen (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2023)
Student satisfaction has long been regarded as a crucial barometer of the standard of management institutions offer in every university. Students are in the best position to determine the kinds of services that an institution will offer because they are the primary recipients of educational services. The study aims to ascertain the degree of customer satisfaction among nursing students concerning the various services offered at the UCLM. The study utilized the non-experimental descriptive-correlation research design. It formulated an aggregate of 250 student respondents on a snowball sampling technique in information gathering from the different year levels in the College of Nursing. The findings revealed that nursing students are delighted with the university's safety and security, its classrooms' standards, and its comfort rooms' use. However, the students felt less satisfied with the opportunities for extracurricular activities, the chance to work on a faculty member's research project, and the campus's free Wi-Fi availability. The study concludes that despite the level of satisfaction perceived by the students, there are still areas for improvement in the delivery of academic experience and usage of various student services. The satisfaction indexed among the students also depicts how well they will perform in their learning experiences in college. The study also concludes that the university's further empowerment among faculty members, besides the facilities being offered, can boost students' academic teaching and learning satisfaction.